Identifikasi Keanekaragaman Jenis Burung di Kawsan Hutan Desa Mata Air,Kecamatan Kupang Tengah, Kabupaten Kupang, Nusa Tenggara Timur - Ardiyanto Namu; Maria M. E. Purnama; Fadlan Pramatana; Muhamad Soimin (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
Mata Air Village Forest Area is located in Kupang Tengah Subdistrict, Kupang Regency, East Nusa Tenggara Province. Mata Air Village has the potential for high diversity of flora and fauna resources, especially bird species because birds have an abundant number of species, easy to observe and wide mobility, but data related to bird diversity and distribution have not been well documented so there is no information about bird diversity in the Mata Air Village area. This study was conducted to determine the level of bird species diversity in the area. This research was conducted from April to May 2024. The method used in this study was the point count method for bird observation. This study was conducted to determine the level of bird species diversity in the area. This research was conducted from April to May 2024. The method used in this study is the point count method for bird observation. The results showed that the birds found in the Mata Air Village Forest Area were 12 bird species from 7 families with a total of 57 individuals. The types of bird food found in the Mata Air Village Forest Area consist of nectivores, insectivores, granivores, frugivores and piscivores. Bird conservation status consists of 10 Least Concern species, 1 Data Deficient species and 1 Near Threatened species. The calculation results using the Shannon-Wienner diversity index obtained a value of H'2.17 where this result is categorized as moderate diversity.